(untitled) (Canadian Medical Education Journal, 2022)
Performance on medical licensing examinations has been previously shown to be predictive of performance in practice. However, licensing examinations are closed-book and real-world medical practice increasingly requires doctors and patients to consult resources to make evidence-informed decisions. To best assess the ability of physicians and physicians-in-practice to avail themselves of point-of-care clinical resources and tools, open-book components may have an emerging role in high-stakes examinations.